Accident cost, speed and vehicle mass externalties, and insurance - Lars Hultkrantz; Gunnar Lindberg (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
Traffic accidents are a human tragedy that kills 1.2 million people worldwide annually (World Health Organization, 2004). The cost of traffic accidents are huge and recent estimates for US alone suggest the cost to be USD 433 billion in year 2000 or 4.3 percentage of GDP (Parry et al, 2007). A reduction of this cost can be done in two ways, either by reducing the number of accidents or by mitigating the consequences of the existing accidents. Insurance systems can contribute to both.
Keywords: 330; Straßenverkehrsunfall; Kraftfahrtversicherung; Externer Effekt